MODEL FUNGSIONALISASI NILAI-NILAI KEARIFAN LOKAL (LOCAL GENIUS) DALAM KEBIJAKAN HUKUM (LEGAL POLICY) DAERAH DI PROVINSI JAWA TENGAH (Kajian Konstitusional Penguatan Komunitas Adat Sedulur Sikep Pati dalam Pengelolaan SDA & Pelestarian LH) - Budiyanto Budiyanto (UNISSULA, 2016)
This study aimed to describe the functional model of the values of local wisdom in the policy area corresponding legal ideals (rechtsideee) of Pancasila. Socio-legal research approach based on constructivism legal paradigm was used to identify the local wisdom Sedulur Sikep and legal policies concerning the construction of Semen Gresik in Sukolilo Pati. The results showed that Sedulur Sikep an indigenous community in the mountains Kendeng who believes that the earth is a biological mother who gives living (hangrungkebi bumi pertiwi), so shall behave harmoniously with its natural surroundings (hamemayu hayuning bawana). Local wisdom of Sedulur Sikep rests on three main values in life (humanity), namely fairness, honesty and truthfulness (propriety) as basis of the rejection of legal policy establishment Semen Gresik in Sukolilo Pati. Therefore, the legal policy areas should be able to accommodate the values of local genius in order to give recognition, respect and protection of the whole of the community customary law in the legal system of the country. The study recommends the concept of “The Law-Society Integrative Framework” as a model for the functionalization of the values of local genius in legal policy areas in the field of natural resource management and environmental conservation. This model is the concept of legal policy futuristic reformative legal foundations by considering the values of local genius is still alive, so as to strengthen the fundamentals of democratic economic environment (ecological), nuanced legitimatif democratic, integrative and social recovery function (social recuperation).